Single-Molecule FRET: A Tool to Characterize DNA Nanostructures - Pal, Nibedita (Frontiers in Molecular Biosciences, 2022)
DNA nanostructures often involve temporally evolving spatial features. Tracking these temporal behaviors in real-time requires sophisticated experimental methods with sufficiently high spatial and temporal resolution. Among the several strategies developed for this purpose, single-molecule FRET (smFRET) offers avenues to observe the structural rearrangement or locomotion of DNA nanostructures in real-time and quantitatively measure the kinetics as well, at the single nanostructure level. In this mini review we discuss few applications of smFRET based techniques to study DNA nanostructures. These examples exemplify how smFRET signals have played an important role not only in characterization of the nanostructures, but also often have helped to improve the design and overall performance of the nanostructures and the devices designed from those structures. Overall, this review consolidates the potential of smFRET in providing crucial quantitative information on structure-function relations in DNA nanostructures.